IDENTITY AND MEMORY VILLAGE TOURISM IN BEMPOSTA - Ferrão, Maria Inês Ferreira Fernandes Pereira; Silva Vidal Saraiva, Alexandra Maria Barros Alves Chaves (European Scientific Journal, ESJ, 2015)
This article was drafted from a wider research that coincided with my master’s thesis, held at Lusíada University of Porto, under the theme “Identidade e Memória - Turismo de Aldeia para Bemposta”, guided by Professor Alexandra Maria Saraiva, in 2013|2014. The aim of this paper is to investigate the importance that Memory and Human Heritage represent to the identity of places and how Man feels the need to seek the identity of its people, from which Man has been separated from. The study developed sets base on an exploratory research method, culminating in a case study in Bemposta, a village located in a Portuguese municipality, Mogadouro. This study is indicative to the widespread desire to return to the origins, and Tourism reveals to be positive in this search for the human nature and its roots, as long as linked to small rural and natural areas, as is the touristic aspect that shows more respect to the preservation of sites. The case study points to the development of an Integrated Village Tourism Network nationwide, recommending its extension to the European scale, with the project for thirteen houses.